Thermolysis and sensitivities of solid propellants using characterized nano oxidizers involving energy performance evaluation - Xiaolan Song; Xiaohui Gao; Yong Kou; Zhihong Yu; Yi Wang; Chongwei An; Fengsheng Li (FirePhysChem, 2022)
This investigation was devoted to exploring the thermal decomposition and sensitivity characteristics of solid propellants using nano-AN and nano-AP as oxidizers. The morphology, surface elements, and crystal structure of nano-AP and nano-AN were investigated by SEM, BET, EDS, and XRD. DSC and TG-MS were used to investigate the thermal decomposition mechanism of nano-AP and nano-AN solid propellants. The mechanical sensitivity of the different solid propellants containing nano-AN and nano-AP was tested and their energy performance was also evaluated. The results show that the microscopic morphology of nano-AN and nano-AP is network-like with the one-dimensional scale less than 100 nm, and the crystal phases of the two are consistent with the raw AN and raw AP, respectively. The thermal decomposition activation energy of AN/CMDB-4 propellant containing nano-AN is 717.46 kJ/mol, while that of AP/HTPB-6 propellant containing nano-AP is 422.33 kJ/mol. The main decomposition products of AN/CMDB-4 propellant are CO2, N2O, NO, CH2O, CO, N2, H2O, CH4 and H2. The products of CO2, N2O, NO, CH2O, CO, N2, H2O, CH4 and H2 are also generated during the decomposition of AP/HTPB-6 propellant. With the increase of nano-AN and nano-AP in propellants, the mechanical sensitivity of AN/CMDB solid propellant decreases, while that of AP/HTPB solid propellant increases. The theoretical standard specific impulse Isp of AN/CMDB and AP/HTPB propellants are 2439.5 N·s/kg and 2449.3 N·s/kg, respectively. The above conclusions show that nano-AP and nano-AN can improve the thermal decomposition performance and the safety of solid propellants, which are expected to be widely used in solid propellants.